Institutional Determinants to Climate Variability Adaptation by Smallholder Irish Potato Farmers in Rubanda District, South Western Uganda - Mugagga, Frank; Elepu, Julius; Nimusiima, Alex; Bamutaze, Yazidhi (American Journal of Climate Change, 2019)
Climate variability and change pose greater challenge not only to human life but to the environment at large. This study sought to evaluate the significance of institutional factors in climate variability adaptation of smallholder Irish potato farmers in Rubanda District, South Western Uganda with the objective of assessing the adaptation measures adopted by smallholder Irish potato farmers, determining the institutional factors that influence adoption of climate variability adaptation measures; and evaluating the institutional challenges that affect the adapting Irish potato farmers. A cross-sectional survey was undertaken to collect data from 197 systematically sampled smallholder farmers from two purposively selected sub counties (Muko and Bubaare) in Rubanda District, using structured questionnaires; whilst key informant interviews were used to elicit data from purposively selected personnel from the local government as well as private and civil society organizations. Multiple linear regression was used to determine the relative influence of selected variables on adaptation measures against climate variability. Results indicate that smallholder Irish potato farmers are adapting to climate variability through agronomic measures such as terracing, mulching, contour ploughing, changing planting dates, early planting, crop-rotation, and technology related measures such as rain water harvesting technologies, adaptive varieties and fertilizers among others. Results from multiple linear regression analysis show that several institutional factors are influencing adoption of climate variability adaptive measures with the most significant ones being access to agricultural extension services, cultivated area and size of land owned. Despite the interventions undertaken, adaptation to climate variability is constrained by the limited access to financial/credit resources and in- adequate technical capacity as well as limited access to information and irregularity of extension services. The study recommends that public and private institutions and personnel, both technical and political, at the various levels of local government, work together to improve extension services, communication as well as enhancing access to credit facilities among smallholder farmers, who will also need to further strengthen existing social groups to enhance their bargaining power.
Keywords: Adaptation; Climate Variability; Institutional Factors; Smallholder Farmers; South Western Uganda